“E colori, gli odori, gli amori, l’Inter, la partita”: il rapporto tra calcio, società e cultura popolare da un’ottica interdisciplinare - Simona Castellano (SHARE Press, 2021)
“Visioni di gioco. Calcio e società da una prospettiva interdisciplinare”, edited by Maurizio Lupo and Antonella Emina, is a volume that collects essays and reflections by scholars belonging to various disciplinary and professional sectors and is part of the panorama of literature that analyzes the relationship between sport and society, proposing a particular vision. The protagonists of the collective volume are stories, events, episodes, anecdotes which, combining considerations of a wider range, show the pervasiveness of football, according to different forms, within society and global culture, highlighting aspects that require adequate investigation.